INHALATION THERAPY - APPROACHES AND CHALLENGES - Bhattacharyya, Sayani; S Sogali, Bharani (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Inhalation therapy is an effective way for local and systemic delivery of miscellaneous drugs for pulmonary and non-pulmonary diseases. The inhalation therapy aims to target specific cells or regions of the lung, bypassing the lung's clearance mechanisms and thereby providing high retention of the drug for longer periods. It helps in improved penetration of intravenously administered antibiotics into lung parenchymal tissue and bronchial secretions, and as a result, their potential systemic toxicity is reduced when given over prolonged periods of time. The advancement in device technology supports the development of more efficient therapy in the form of delivering finer particles into the lung in large doses. Therefore, meticulous daily management of lung disease, together with prompt, aggressive treatment of exacerbations can be achieved through inhalation to preserve lung function. This review summarizes the features of inhalation delivery devices, their advantages and limitations, challenges in formulation and brief description of novel technologies currently marketed.